2009
DOI: 10.1038/ejhg.2009.165
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of a panel of single-nucleotide polymorphisms in microRNA genomic regions for association studies in human disease

Abstract: MicroRNAs (miRNA) are recognized posttranscriptional gene repressors involved in the control of almost every biological process. Allelic variants in these regions may be an important source of phenotypic diversity and contribute to disease susceptibility. We analyzed the genomic organization of 325 human miRNAs (release 7.1, miRBase) to construct a panel of 768 single-nucleotide polymorphisms (SNPs) covering B1 Mb of genomic DNA, including 131 isolated miRNAs (40%) and 194 miRNAs arranged in 48 miRNA clusters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
3
21
1
Order By: Relevance
“…Nevertheless, our analysis of currently available data revealed a much higher frequency (5.9%) of miR-seed polymorphisms in human than the frequency of >1% reported by Didiano and Hobert [46]. Similarly, Muiños-Gimeno et al [47] also revealed much lower frequencies than our study mapping 24 SNPs within 325 mature miRNAs and detecting only two miR-seed-SNPs. They also estimated the density of SNPs in miRNAs to be 4.5-times lower that in the rest of the genome [47].…”
Section: Resultscontrasting
confidence: 70%
“…Nevertheless, our analysis of currently available data revealed a much higher frequency (5.9%) of miR-seed polymorphisms in human than the frequency of >1% reported by Didiano and Hobert [46]. Similarly, Muiños-Gimeno et al [47] also revealed much lower frequencies than our study mapping 24 SNPs within 325 mature miRNAs and detecting only two miR-seed-SNPs. They also estimated the density of SNPs in miRNAs to be 4.5-times lower that in the rest of the genome [47].…”
Section: Resultscontrasting
confidence: 70%
“…Findings of this study also showed 2 miRNA regions, hsa-mir-26a-2 in the The role of miR-26 in tumors and normal tissues (Review) JIE GAO and QING-GUANG LIU CTDSP2 gene and hsa-mir-128-1 in the R3HDM1 gene, among a Spanish population (16). Concomitantly, Diederichs and Haber reported that the expression levels of miRNAs were globally reduced in cancer compared with matched normal tissues.…”
Section: Processing and General Functions Of Mirnasmentioning
confidence: 71%
“…The SNP −631 G > T (rs28915400) and −318 G > C (rs4919859) located in the 5 -Flank and 10141 G > A (rs8637), 10826 G > A (rs6758) occurred in the 3 -untranslated region of the BSG gene, the SNP at the 3 -untranslated region or 5 -flanking may affect gene expression at the post-transcriptional level by interfering protein binding, polyadenylation or miRNA binding [34,35]. By compared with the allele frequencies of these BSG polymorphisms in Chinese and other populations as deposited in the Hapmap database, we observed obvious different in allelic and genotype distribution for the polymorphisms, we think the functional significance of these SNP should be deserved further study.…”
Section: Snps Site Selectionmentioning
confidence: 99%